Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.2754/avb200574040613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraarticular Bupivacaine Administration on Postoperative Pain Relief after Arthrotomic or Arthroscopic Management of Cranial Cruciate Ligament Rupture in Dogs

Abstract: The goal of the study was to disclose superiority of either arthroscopy or arthrotomy in the treatment of CCL rupture with respect to post-surgical pain, to find whether bupivacaine administered intraarticularly is of any value in reducing postoperative pain, and through the present pain scoring system consisting of degree of the lameness, CPS and VAS to recommend therapeutical plan of CCL repair offering the better analgesia.Thirty-seven dogs with cranial crucial ligament (CCL) rupture were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…A anestesia epidural é indicada para procedimentos cirúrgicos nos membros pélvicos, coxal, região anal, perineal e caudal (RAUSER et al, 2005;SKARDA, 1996), cirurgias retro umbilicais como, cesariana, ovariohisterectomia, redução de prolapsos, caudectomia, orquiectomia e osteossíntese em membros pélvicos (LUNA, 2005).…”
Section: Anestésicos Aplicados Pela Via Epiduralunclassified
“…A anestesia epidural é indicada para procedimentos cirúrgicos nos membros pélvicos, coxal, região anal, perineal e caudal (RAUSER et al, 2005;SKARDA, 1996), cirurgias retro umbilicais como, cesariana, ovariohisterectomia, redução de prolapsos, caudectomia, orquiectomia e osteossíntese em membros pélvicos (LUNA, 2005).…”
Section: Anestésicos Aplicados Pela Via Epiduralunclassified
“…Intra-articular injection of local anaesthetics with adjuvants has been introduced as an alternative to post-operative analgesia (Rauser et al 2005;Vintar et al 2005), and most studies con-ducted to date have reported that intra-articular injection of a drug is sufficiently effective for diagnostic procedures (Boden et al 1994;Convery et al 1998;Moiniche et al 1999;Rauser et al 2005). Ropivacaine (s-(-)-l-propyl-2',6'-pipecoloxylidide hydrochloride monohydrate) is a new amide local anaesthetic single isomer drug (McCrae et al 1995).…”
mentioning
confidence: 99%